Interview on the #Charlestonsyllabus - Williams, Chad; Williams, Kidada E.; Blain, Keisha N. (Radical Teacher, 2016)
In this interiew, the three history professors who started the #CharlestonSyllabus Twitter hashtag–Chad Williams, Keisha N. Blain, and Kidada Williams–discuss the significance of the reading list and subsequent book for educators and members of the general public.